A comparative and prospective study of ventral hernia repair by laparoscopic and open technique - Kumar, Abhishek; Chumber, Sunil (International Journal of Research in Medical Sciences, 2024)
Background: Ventral hernia repair is becoming more common through laparoscopic techniques; however, there is a lack of comprehensive data on the associated complication rates. We undertook a prospective study to contrast the early establishments of laparoscopic and open ventral hernia surgeries in order to fill this gap. The aim of the study was to assess and contrast the efficiency and reliability of open and laparoscopic techniques for the treatment of ventral hernias. Methods: A prospective study was carried out at All India Institute of Medical Science, New Delhi, India between 2011 and 2014 to assess the dissimilarities between open and laparoscopic approaches in ventral hernia repairs. The study included a total of 40 cases each for open/laparoscopic ventral hernia repair procedures. Results: Eighty cases were investigated, forty of which underwent open repairs and forty of which underwent laparoscopic procedures. In this study, the oldest patient was 77 years old, and the youngest patient was 25 years old. The vast majority (49%) of patients were in their fourth to sixth decades of life. Incisional hernias were in bulk, that had formed from earlier midline lower scars. In both open and laparascopic surgery, there were 40 patients- 43 females and 37 males. Conclusions: Ventral hernia repair via laparoscopic surgery is showing encouraging results and is currently a widely used technique. When compared to open repairs, it has benefits like decreased postoperative pain, shorter hospital stays, and fewer short-term problems. Laparoscopic hernia surgery also results in a lower risk of wound infections, an earlier restoration of bowel function, and a quicker return to regular activities.